Rôles des mangroves, modes et perspectives de gestion au Delta du Saloum (Sénégal) - Ngor Ndour; Sara Danièle Dieng; Mamadou Fall (VertigO)
This study allowed determining diverse roles of the mangrove in Delta du Saloum. To the ecological plan, the slightest environmental changes are harmful to mangrove (Ndour, 2005 ; Thomas and al., 1997 ; Blasco, 1983). The consequences are their degradation and the loss of the functions of nurseries, housing environment and niche ecological. In the socioeconomic aspects, mangrove exploitation resources make them playing the role of rampart of the livelihood of the coastal populations (Sène, 2007 ; Cormier-Salem, 1999). So, the goods and services which the mangrove procures to population, gets created divergent interests between the various actors ; what makes difficult their management. Among others obstacles, there is their sector-based management which implies at once several state services. This sector-based approach not facilitates harmonization of the measures of preservation. Otherwise, in spite of the existence of several plans of management, there is always no transfer of competence in fishery domain which prevents in a part the actors to play entirely their roles. In these conditions, perspectives of mangroves management should turn around the harmonization of the measures of protection, decision-making by the Ministry of fishery on marine resources, the elaboration of landscaping of classified forests and codes for good behavior in the area. This need also to promote joint management including the neighboring States sharing the same resources (Ndour, 2005).